2014
DOI: 10.1371/journal.pone.0100941
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Escherichia coli Outer Membrane Biogenesis Using Differential Proteomics

Abstract: The cell envelope of Gram-negative bacteria is a complex multi-layered structure comprising an inner cytoplasmic membrane and an additional asymmetric lipid bilayer, the outer membrane, which functions as a selective permeability barrier and is essential for viability. Lipopolysaccharide, an essential glycolipid located in the outer leaflet of the outer membrane, greatly contributes to the peculiar properties exhibited by the outer membrane. This complex molecule is transported to the cell surface by a molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 83 publications
(132 reference statements)
3
25
0
Order By: Relevance
“…2A). In keeping with this finding, our previous transcriptomics results showed that colistin treatment up-regulated the expression of the Mla system ( M aintenance of OM l ipid a symmetry) in A. baumannii ATCC 19606, which is responsible for transporting excess phospholipids in the outer leaflet back to the inner membrane to maintain the OM asymmetry415152. Significant changes to the OM lipids, as observed at both the transcriptomics and metabolomics levels, are highly consistent with the proposed bactericidal mechanism of colistin via lipid exchange between the inner and outer membrane11.…”
Section: Discussionsupporting
confidence: 63%
“…2A). In keeping with this finding, our previous transcriptomics results showed that colistin treatment up-regulated the expression of the Mla system ( M aintenance of OM l ipid a symmetry) in A. baumannii ATCC 19606, which is responsible for transporting excess phospholipids in the outer leaflet back to the inner membrane to maintain the OM asymmetry415152. Significant changes to the OM lipids, as observed at both the transcriptomics and metabolomics levels, are highly consistent with the proposed bactericidal mechanism of colistin via lipid exchange between the inner and outer membrane11.…”
Section: Discussionsupporting
confidence: 63%
“…Notably, the same mlaA in-frame deletion (named mlaA*) has been recently isolated as responsible for suppressing the bacitracin sensitivity of an lptD mutant defective in LPS assembly at the OM (44). Moreover, the IM MlaD protein increases in abundance in cells where LPS transport is severely impaired (63). These findings further strengthen a functional link between the Mla system and the Lpt machinery.…”
Section: Discussionmentioning
confidence: 75%
“…For this we induced severe OM assembly stress by depleting LptC, an essential component of the lipopolysaccharide (LPS) export machinery. It is known that E. coli arrests growth but is capable to survive the depletion of lptC (25). We grew cells of BW25113araBplptC in the presence of arabinose and then inoculated them into growth media with or without arabinose, and in the presence or absence of copper chloride, and followed cell growth (optical density, OD) and viability (colony forming units, CFU) ( Fig.…”
Section: Resultsmentioning
confidence: 99%